Post-Pandemic Covid-19 Strategies for Iron and Metal Workshops When the Country of Indonesia is Under the Threat of 2023 Global Recession - Vicki Dwi Purnomo (Jurnal Ekonomi dan Bisnis Digital, 2023)
This research is a reality in the field related to the Iron and Metal handicraft industry which has been going on for quite a long time. Iron and metal handicraft centers initially only produced household furniture items until now they have penetrated into agricultural equipment, plantations and so on, with the increasing number of requests from various business sectors, Iron and Metal Crafts in Bendungan Village, Dusun Kuncen, are still very slow in development compared to MSMEs other. Even though during the initial field observation, in terms of the expertise of the workforce and the tools used were modern. The purpose of this study is to determine the development and factors that hinder the development of the iron and metal craft business. This study used a qualitative descriptive method, in which the author immediately went down to the field to conduct interviews with iron and metal craftsmen. While the sampling technique used in this study was interviews. The results of this study indicate that the development factor for the iron and metal handicraft industry is determined by the skills of the craftsmen themselves, the use of machines, the ease of obtaining raw materials and product quality.